Strategi Kepemimpinan Kepala Madrasah dalam Era Digital: Meningkatkan Kinerja Pendidik dan Prestasi Siswa - Asyafi'iyah, Nani; Nur, Irawati (Amsir Management Journal, 2024)
This study examines the role of madrasah heads in improving teacher performance at Madrasah Ibtidaiyah PSM Jerukgulung using a qualitative approach. The results of the study show that the head of the madrasah plays the role of educator, supervisor, leader, manager, motivator, and innovator. These roles are realized through involvement in teacher quality improvement, classroom visits, decision-making, cooperation, coordination, planning, awarding, and discipline enforcement. However, there are several obstacles such as human resource and time management, difficulty understanding teacher characteristics, and educational supervision